Tracing the Origin of Invasive Fungal Infections. Issue 4 (April 2020) - Papon, Nicolas; Bougnoux, Marie-Elisabeth; d'Enfert, Christophe
Abstract : Invasive fungal infections are a major cause of mortality in immunocompromised patients. By using high-resolution sequencing, Zhai et al . provide insight into translocation of Candida strains from the gut mycobiota to the bloodstream of transplanted patients. Microbiota-driven diagnostic methods could rapidly emerge for preventing deadly fungal infections.